(untitled) (Research, Society and Development, 2021)
Introduction: The human intestinal microbiota has a fundamental role in maintaining health and preventing diseases such as obesity. It is known that there is a correlation between both, since this clinical condition leads to Intestinal Dysbiosis. And, the therapy also involves an intestinal modulation with prebiotics and probiotics. Objective: To describe the importance of the balance of the intestinal microbiota in the prevention and treatment of obesity. Methodology: This is a bibliographic review with a descriptive approach. Results: From the literature study, it was possible to observe that in addition to the influence of anatomical and physiological factors, there are multifactorial causes that lead the individual to obesity, such as the imbalance of the intestinal microbiota, as well as bad eating habits. Discussion of the results: The effective existence of a correlation between the Intestinal Microbiota and Obesity caused by the type of diet of the individual, medicine misuse, foods rich in FODMAPs and which can be dealt with changes in lifestyle and intestinal modulation. Conclusion: Through the studies carried out, it was possible to prove the importance of maintaining the intestinal microbial balance in order to avoid clinical complications and improve the prognosis of the obese individual.